The Effect of Budget Planning, Budget Implementation, the Competency of Human Resources and Understanding of Regulation on Village Financial Budget Absorption with Organizational Commitment as Moderating Variable - Yona Oktari; Ria Nelly Sari; M. Rasuli (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to examine and analyze the effect of budget planning, budget implementation, the competency of human resources and understanding of regulation on Village Budget Absorption with organizational commitment as moderator. The population in this study is 136 villages in Bengkalis Regency and the sample was determined by Saturated Sampling technique. The Village Chief, Village Secretary (Sekdes), Planning and Finance Section participated as respondent. Data were analyzed by using Moderated Regression Analysis. The results of this study shows that budget planning, budget implementation, the competency of Human Resources and understanding of regulations affect the village budget absorption. Futhermore, the result shows thatorganizational commitment strengthen the effect of village financial budget absorption.